2019
DOI: 10.1155/2019/8659138
|View full text |Cite
|
Sign up to set email alerts
|

The Variations of Satellite-Based Ecosystem Water Use and Carbon Use Efficiency and Their Linkages with Climate and Human Drivers in the Songnen Plain, China

Abstract: Ecosystem water use efficiency (WUE) and carbon use efficiency (CUE), as two of the most important ecological indicators of an ecosystem, represent the carbon assimilation rate of unit water consumption and the capacity of transferring carbon from the atmosphere to potential carbon sinks. Revealing WUE and CUE changes and their impact factors is vital for regional carbon-water interactions and carbon budget assessment. Climate affects carbon and water processes differently. Compared to WUE, the variations in C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…We compared the CUE calculated by the same model of different ecosystems at the annual scale from other reported studies (Table 4). The order of annual CUE of different ecosystems in SNP was as follows: GRA (0.567) > WET (0.542) > MF (0.480) > DBF (0.479) [19]. Tang et al [3] found the largest CUE for WET on a global scale.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…We compared the CUE calculated by the same model of different ecosystems at the annual scale from other reported studies (Table 4). The order of annual CUE of different ecosystems in SNP was as follows: GRA (0.567) > WET (0.542) > MF (0.480) > DBF (0.479) [19]. Tang et al [3] found the largest CUE for WET on a global scale.…”
Section: Discussionmentioning
confidence: 97%
“…The trend analysis method was used to analyze trend in seasonal CUE changes for the period 2001-2015. The outputs of the trend analysis are the maps of regression slope values, expressed by the following formula [19]:…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides ND and CO 2 (Figure S2), various other factors also have profound effects on CUE and WUE at different temporal and spatial scales. The temperature and precipitation factors also showed an upward trend; rising air temperature decreased the CUE ratio, and increased precipitation led to an increase in the CUE ratio [52][53][54][55][56][57][58][59]. In environmental conditions, temperature, precipitation, solar radiation, etc, are all key climate-change factors that affect the WUE of ecosystems [60].…”
Section: Effect Of Residual Factors On Cue and Wuementioning
confidence: 99%